Cardiac cell modelling: observations from the heart of the cardiac physiome project - Fink, Martin; Niederer, Steven A.; Cherry, Elizabeth M.; Fenton, Flavio H.; Koivumäki, Jussi T.; Seemann, Gunnar; Thul, Ruediger; Zhang, Henggui; Sachse, Frank B.; Beard, Dan; Crampin, Edmund J.; Smith, Nicolas P. (Elsevier, 2011)
In this manuscript we review the state of cardiac cell modelling in the context of international initiatives such as the IUPS Physiome and Virtual Physiological Human Projects, which aim to integrate computational models across scales and physics. In particular we focus on the relationship between experimental data and model parameterisation across a range of model types and cellular physiological systems. Finally, in the context of parameter identification and model reuse within the Cardiac Physiome, we suggest some future priority areas for this field.